The Influence of the Implementation of Islamic Business Ethics on Business Competitiveness in MSMEs in Bima City - Karmila Karmila; Ichwan P. Syamsuddin; Rafiuddin Rafiuddin (STKIP Taman Siswa Bima, 2025)
The application of Islamic business ethics in business activities is an important aspect in building the competitiveness of Usaha Mikro, Kecil, dan Menengah (UMKM) in Bima City. In the context of increasingly competitive business competition, the application of Islamic principles such as honesty, justice, responsibility, and not committing fraud is a foundation that can increase consumer confidence and business blessings. This study aims to determine the real effect of the application of Islamic business ethics on the competitiveness of UMKM in Bima City. The method used is a quantitative approach with survey techniques, distributing questionnaires to 40 UMKM players in various business sectors. Data were analysed using simple linear regression to measure the relationship between Islamic business ethics variables and business competitiveness. The results showed that the application of Islamic business ethics has a positive and significant effect on increasing competitiveness. The key points found were: (1) honesty increases customer loyalty, (2) fairness in transactions strengthens long-term business relationships, (3) trustworthiness and responsibility create a good business image, and (4) avoiding fraudulent practices avoids social and legal sanctions. With the application of Islamic ethics, UMKM are not only able to survive but also thrive in the face of market challenges. This research recommends the importance of Islamic ethics-based training and mentoring for UMKM actors to create a healthy and competitive business ecosystem.